Wide-open town : Kansas City in the Pendergast era - Burke, Diane Mutti; Roe, Jason; Herron, John P., 1968- (University Press of Kansas, 2018)
"Wide-Open Town explores the rich history of Kansas City in the interwar period, which has been characterized as an exciting period of growth, development, and cultural fluorescence--the city's Golden Age--even in the midst of rampant public corruption, economic depression, and strained social relations. The contributors to this wide-ranging collection seek to answer the question of whether this really was Kansas City's Golden Age: did this era elevate, refine, or ruin Kansas City's national profile? The contributors come from a variety of departments and institutions, and chapters focus on such topics as the 1928 Republican National Convention, the KC Monarchs, Mexican immigrants, drag shows, health care, the stockyards, and Thomas Hart Benton--and, of course, jazz"--